2019
DOI: 10.3389/fnins.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Local Diffusion Homogeneity Provides Supplementary Information in T2DM-Related WM Microstructural Abnormality Detection

Abstract: Objectives: We aimed to investigate whether an inter-voxel diffusivity metric (local diffusion homogeneity, LDH), can provide supplementary information to traditional intra-voxel metrics (i.e., fractional anisotropy, FA) in white matter (WM) abnormality detection for type 2 diabetes mellitus (T2DM).Methods: Diffusion tensor imaging was acquired from 34 T2DM patients and 32 healthy controls. Voxel-based group-difference comparisons based on LDH and FA, as well as the association between the diffusion metrics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
7
11
0
2
Order By: Relevance
“…Increased level of LDH, as mentioned earlier, reflects the adverse effects of diabetes. The association between LDH and BMI among diabetic patients in our study is in line with other studies ( 15 - 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…Increased level of LDH, as mentioned earlier, reflects the adverse effects of diabetes. The association between LDH and BMI among diabetic patients in our study is in line with other studies ( 15 - 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…Higher FCs indicate the enhancement of temporal consistency of the different brain regions. In the present study, increased FC based on the hub DC analysis was found not only within different cerebellar regions but also between ipsilateral cerebrocerebellar regions, suggesting sophisticated recruitment capacity of the cerebellum in T2DM (15,42,43). Though the cognitive functions of the cerebellum are not yet well-understood, a study based on exceptionally large and high-quality dataset analysis indicated that functional gradients of the cerebellum correspond to intrinsic connectivity of cerebellar voxels with the rest of the cerebellum (49).…”
Section: Functional Connectivity Alteration In Type 2 Diabetes Mellitussupporting
confidence: 51%
“…However, some previous studies reported that T2DM subjects showed significant decreased anatomical connections, mean regional homogeneity (mReHo), cerebral blood flow (CBF), and DC in cerebellar regions ( 46 48 ), providing evidence to the significant role of the cerebellum in terms of cognitive function. Although inconsistent results were obtained, it is believed that the cerebellum might play an important role in maintaining normal cognitive functions in T2DM before the onset of symptoms or even at the prediabetic stage ( 15 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations